Investigation of the light output of 3D-printed plastic scintillators for dosimetry applications. (November 2022) - Kapłon, Ł.; Kulig, D.; Beddar, S.; Fiutowski, T.; Górska, W.; Hajduga, J.; Jurgielewicz, P.; Kabat, D.; Kalecińska, K.; Kopeć, M.; Koperny, S.; Mindur, B.; et al.
Abstract: Three-dimensional (3D) printing, specifically digital light processing (DLP) technique, can be used to manufacture plastic scintillators of any shape. The purpose of this study was to determine the light output of DLP 3D-printed scintillators for dosimetry applications. Two types of plastic scintillators with dimensions 10 mm × 10 mm × 10 mm were fabricated using DLP 3D-printing at Hanyang University, South Korea. The light output of these DLP 3D-printed samples was measured and compared to that of a commercial plastic scintillator of the same dimensions, RP-408, produced by casting. The 3D-printed scintillators emitting violet and blue light had a lower relative light output by 49% and 43%, respectively, compared to the RP-408 reference scintillator. We also investigated three types of scintillator surface finishing methods: the original surface made by the 3D printer, a sanded surface, and a polished surface. Furthermore, three wrapping configurations were tested: bare scintillator, diffuse-type polytetrafluoroethylene tape, and specular-type enhanced specular reflector foil. Both reflector types, diffuse and specular, reflected blue light with comparable efficiency. Additionally, emission and transmission spectra of the samples were measured. Emission maxima were located at 430 nm for RP-408, and 438 and 475 nm for two 3D-printed samples. Transmittance at the wavelength of maximum emission was equal to 89% for RP-408, and 73% and 66% for the two DLP-printed samples. Although the light output of the 3D-printed scintillators was about 50% lower than that of the commercial plastic scintillator, due to characteristics of 3D-printed plastic scintillators, i.e. fast, low-cost production, and easy customization of the printed shape, they are promising as an active part of dosimeters for use in high intensity gamma radiation fields produced by medical linear accelerators with acceptable signal-to-noise ratio level. Highlights: 3D printing technique was used to manufacture plastic scintillators. Light output of three types of blue-emitting plastic scintillators was measured. Original, sanded and polished scintillator surface finishes were investigated. Diffuse and specular reflectors have comparable light reflection efficiency. 3D-printed scintillators are sufficient for use in dosimetry in radiation therapy.